Comunidades de macroinvertebrados acuáticos y calidad hídrica en el rio Quevedo, Ecuador - Barragán Vargas, Jhon Javier (2018)
In the present research project, the water quality of the Quevedo River was evaluated, taking as aquatic macro-invertebrate bioindicators (MA) and in turn, it was determined the quality levels of the waters. The importance of research is to establish the composition of benthic macro-invertebrates and to evaluate the current degree of ecological impact in which the Quevedo River is located, through the study of aquatic macro-invertebrate communities in three Sections: Palo Blanco, Holandesa-Camarones y San Francisco, And the incidence of the types of use agricultural land, forest and pasture (respectively), according to the degradation of the effluents. The aquatic macro-invertebrates in the different sections of the river Camarones Quevedo, a total of 918 macro-invertebrates were obtained between 36 genera and 6 orders, where the greater quantity of MA in forest was evidenced with 39% of the total population, followed by pasture With a 32%, and finally with a 29% agricultural. The quality of the fluvial habitat and the vegetation status of the banks of the river Quevedo were determined by the application of the Fluvial Habitat Index (IHF) and the Calid index While the biological index BMWP-CR which evaluates the quality of water, determined that in the river Quevedo (in the 3 sections) the quality of bad water. With respect to the indices of diversity, wealth, dominance of Shannon, Margalef and Simpson, based on the use of soil, determined that forest was the use of predominant soil given that it obtained greater richness between the indexes obtaining higher values as opposed to Agriculture and pasture. Keywords: Aquatic macro-invertebrates, land uses, quality indexes, anthropogenic activities.